2020
DOI: 10.47577/technium.v2i7.1644
|View full text |Cite
|
Sign up to set email alerts
|

Influence of propulsion installation performance on travel efficiency

Abstract: This paper presents an analysis of exploitation parameters for naval propulsion plant at different operating regimes. For naval propulsion plant with internal combustion engines, is considered as independent variables which give its operating regimes. Functional parameters of analysis of navigational regimes considered representative of the operation of the ship. Propulsion of the ship is provided by a fixed pitch propeller that allows modification propulsion performance by adjusting a single parameter functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The (14) and (15) there can be observed that for rising of the intake air in amount of 6 [°C] (for example: from -3 [°C]to +3 [°C]) is needed a compressed airwith a mass flow equal with 1.32 [kg/s] from the LP system (but this amount of mass flow is not allowed to be extracted from the gas turbine LP compressor because it represented about 8.57 [%]from the total intake air mass flow) but, at the other hand the anti-icing can be achieved by using compressed air from the HP systemwith mass flow equal with 0.75 [kg/s] which is about 4.48[%]from the total intake air mass flow.…”
Section: Thermal Anti-icing System -Proposalmentioning
confidence: 99%
“…The (14) and (15) there can be observed that for rising of the intake air in amount of 6 [°C] (for example: from -3 [°C]to +3 [°C]) is needed a compressed airwith a mass flow equal with 1.32 [kg/s] from the LP system (but this amount of mass flow is not allowed to be extracted from the gas turbine LP compressor because it represented about 8.57 [%]from the total intake air mass flow) but, at the other hand the anti-icing can be achieved by using compressed air from the HP systemwith mass flow equal with 0.75 [kg/s] which is about 4.48[%]from the total intake air mass flow.…”
Section: Thermal Anti-icing System -Proposalmentioning
confidence: 99%